Soft contact lens parameter changes after using the lens2¨ automated lens cleaner machine - Haliza Abdul Mutalib,; Kang, Chye Lee (Universiti Kebangsaan Malaysia, 2010)
Disinfection of contact lens is an important procedure strongly emphasized by eye care practitioners. There are several types of disinfecting methods. Some methods have been proven to induce parameter changes on soft lenses. These parameter changes are likely to affect the efficacy of contact lens fitting and patients comfort. A self-controlled trial was carried out on a series of disposable soft contact lenses of different material to evaluate parameter changes after cleaning with Lens2¨ (Automated Lens Cleaner Machine). This will be compared to the lens cleaned conventionally (digital rubbing). Fifty four pieces of soft contact lenses were divided into 2 groups; cleaned conventionally and with Lens2¨. Three types of soft contact lenses of different materials were used; Soflens®38, Focus® Monthly and O2 Optix. Each contact lens was cleaned for 30 times to mimic the period of 30 days wear. After the thorough cleaning process, the back optic zone radius (BOZR), back vertex power (BVP), central thickness(ct) and total diameter (TD) were measured. The parameters were statistically analysed to evaluate the changes. There were significant changes in the TD and BVP of Soflens®38 and O2 Optix with both methods. The Focus® Monthly contact lens only showed significant BOZR changes with both methods. However, these parameter changes were not clinically significant because the changes were still in the tolerance range set by ISO (International Organization of Standardization). Both cleaning methods proved to maintain lens parameter within its acceptable range.